L’alienazione estetica nell’overtourism e nel turismo 4.0 - Terrosi, Roberto (Scenari, 2025)
This paper examines how contemporary tourism practices, particularly overtourism and Tourism 4.0, represent a profound alienation of the aesthetic experience. Starting from the historical origins of tourism in the Grand Tour tradition, we analyze how the aesthetic dimension of travel has undergone multiple stages of alienation, from the initial commodification of cultural experiences to the current situation where the experience itself becomes a commodity. The article argues that while overtourism and Tourism 4.0 appear to be opposing phenomena, they are two sides of the same coin, both resulting from a degradation of the aesthetic dimension despite their connection to experiences that maintain a fundamental relationship with aesthetics. Through a theoretical framework that draws from classical alienation theory (from Rousseau to the Frankfurt School), we demonstrate how the current tourism industry not only alienates the aesthetic experience but reduces it to waste, transforming portions of tourists’ lives into mere packaging devoid of the promised emotional content. This analysis reveals how the commodification of experience in contemporary tourism represents a new frontier in the alienation of human experience.